2013
DOI: 10.1021/jp4054605
|View full text |Cite
|
Sign up to set email alerts
|

IR Absorptions of C60+ and C60 in Neon Matrixes

Abstract: C60(+) ions were produced by electron-impact ionization of sublimed C60, collimated into an ion beam, turned 90° by an electrostatic deflector to separate them from neutrals, mass filtered by a radio frequency quadrupole, and co-deposited with Ne on a cold 5 K gold-coated sapphire substrate. Infrared absorption spectroscopy revealed the additional presence of C60 and C60(-) in the as-prepared cryogenic matrixes. To change the C60(+)/C60(-) ratio, CCl4 or CO2 electron scavengers were added to the matrix gas. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 26 publications
7
77
1
Order By: Relevance
“…The UHV experimental setup for optical spectroscopy of mass-selected species has already been described in our previous publications [9,19,20]. Briefly, C longpass filter (Thorlabs FELH0950) was used to detect the emission.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The UHV experimental setup for optical spectroscopy of mass-selected species has already been described in our previous publications [9,19,20]. Briefly, C longpass filter (Thorlabs FELH0950) was used to detect the emission.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The IR and UV-NIR absorption spectra of C +/− 60 (Kern et al 2013) and C 2+/3+ 60 (Kern et al 2014) have been reported previously along with experimental procedures and data analysis methods. Briefly, samples were prepared through low-energy ion beam deposition into a cocondensed inert gas matrix doped with electron scavengers (CO 2 , CCl 4 ) as necessary to vary the resulting fullerene charge state distributions.…”
Section: Experiments and Observationsmentioning
confidence: 99%
“…Absorptions of different C 60 charge states are indicated with 0, + and -for neutral, cation, and anion, respectively. been described in detail in our previous work (Kern et al 2013(Kern et al , 2014. IR frequencies of C 60 , C + 60 , and C − 60 absorptions in Ne and Ar matrixes are presented in Table 1 together with Ne data for C so far, we estimate the low-temperature gas-phase absorption frequencies from the matrix data.…”
Section: Laboratory Ir Datamentioning
confidence: 99%
See 2 more Smart Citations